Multidrug-resistant pathogens isolated from ready-to-eat salads available at a local market in Pakistan. Issue 8 (1st August 2016) - Ilyas, Sana; Qamar, Muhammad Usman; Rasool, Muhammad Hidayat; Abdulhaq, Nazia; Nawaz, Zeeshan
Abstract : Purpose: This manuscript aims to evaluate the frequency and antimicrobial susceptibility pattern of pathogens present in ready-to-eat salads available at a local market. Design/methodology/approach: A 100 salad samples were collected aseptically. Each sample (25g) was homogenized in 225ml of sterile peptone water and was serially diluted up to 1x106. Dilutions were inoculated on nutrient agar by surface spread plate technique. Aerobic colony count (ACC) was estimated by counting the colonies. Bacterial isolates were cultured on blood and MacConkey agar and identified on the basis of their morphology, culture characteristics and confirmed by API 20E and 20NE. Antimicrobial susceptibility was determined as per CLSI 2014. Findings: ACC range was 1.1x103 cfu/g to 5.8x109 cfu/g. Among these the highest ACC was found in channa chat (4.9x104 to 5.8x109 cfu/g). A total of 127 microorganisms were identified; 73 were Gram negative rods and 24 were Gram positive cocci. Among GNRs; Klebsiella spp. (n=18) was the predominant whereas among GPC, Staphylococcus aureus (n=6) were the chief pathogen. Klebsiella spp. showed 100% resistance to ampicillin, 89% to 78% to amoxicillin/clavulanic acid and 33% to imipenem however Enterobacter spp. were resistant to ampicillin (100%) amoxicillin/clavulanic acid (77%) and imipenem (23%). Staphylococcus aureus showed resistance to co-amoxiclav (83%) and penicillin (75%). Practical implications: This study revealed that effective control measures must been implemented and respected by throughout the entire food chain and better surveillance studies should be performed at national level to reduce the spread of bacteria by fresh salads. Originality/value: This paper explore the high prevalence of MDR pathogens in different salads and most of the salads were found to be unhygienic for consumption.